Measurements of soil gas radon in active fault systems: A case study along the North and East anatolian fault systems in Turkey - Inceöz, M; Baykara, O; Aksoy, E; Dogru, M (Pergamon-Elsevier Science Ltd, 2006)
We have used solid-state nuclear track detectors (CR-39) in order to determine the profile of the soil radon in district areas of the North and East Anatolian active fault systems in Turkey. It has been shown that the radon anomalies among the fault zones are relatively high in the fault line while dramatically decreases by going away from the lines. Radon concentrations in both active fault systems ranged from 4.3 to 9.8 kBq m(-3). The average radon concentration levels in the North Anatolian Fault System are relatively higher than the East Anatolian Fault System. Radon measurement technique is proved to be a good tool for detection and mapping of the active fault zone, and also in the case of continuous monitoring of radon anomalies connected with earthquake events. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: radon; CR-39; fault zone; NAFS; EAFS